Relationship between Static Alignment of the Foot and Dynamic Balance in College Baseball Players - YASUDA, Ryoko; KURIHARA, Toshiyuki; ISAKA, Tadao; SHINOHARA, Yasushi (Rigaku ryoho kagaku, 2021)
[Purpose] The purpose of this study was to examine the relationship in college baseball players between static alignment of the foot and dynamic balance in terms of the foot (pivoting, stepping) and position (pitcher, fielder). [Participants and Methods] The participants were 106 college baseball players (31 pitchers, 75 fielders). The static foot alignment indexes were the medial longitudinal arch height, the lateral angles of the first and fifth toes, the angle between the first and fifth toes, and the foot width/length ratio in the standing position, and the dynamic balance index was defined as the stabilization time of the center of gravity. [Results] The foot width/length ratio of the stepping foot of the pitchers was shorter than that of the fielders. There were no significant differences in dynamic balance between the positions. A significant correlation was found between the stepping foot width and the stepping foot width/length ratio and the time to stabilize the center of gravity after the forward stepping motion for the pitchers only. [Conclusion] The result suggests that the pitcher may reduce the load on the stepping foot and stabilize it by stiffening the forefoot lateral arch after the stepping foot contacts the ground.